Barriers and facilitators in the meticulous compilation and adaptation of standardised nursing care plans in a public hospital of the Eden district, South Africa : a nursing perspective - Van As, Saria (Stellenbosch : Stellenbosch University, 2018)
Thesis (MNur)--Stellenbosch University, 2018.